TRIPLE ROLES CONFLICT: EQUITY OF WORK - FAMILY LIFE BALINESE WOMEN’S - Kadek Dilan Ari Rahayu , A.N Oka Suryadinatha Gorda , A.N. Eddy Supriyadinatha Gorda , A.N. Sri Rahayu Gorda (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Women of 21st century do not only embrace in two but three roles at once in so called triple roles. These involve family role, economic role, and social role. Role imbalance might lead to clash in terms of internal or external conflict and this will also inflict a penalty or sanction. The objective of this study is to gain a more thorough insight on triple roles conflict dealt by female employees especially married Balinese women that have bore children in Tibubeneng Village Chief Office. Qualitative research method was utilized and combined with case-study model approach. Data analysis in this study includes scrutinizing the results of observation, interview sessions, and documentation obtained by the assistance of software QSR NVivo 12 Plus. From the data processes, the conclusion that can be drawn is the fact of 8 main nodes appeared in this study such as: conflict, family, conflict handling, work, role, customs, time management, and Balinese women. Conflict as one of the main nodes was dominating the data collected by author indicating that clashes or role conflict primarily to women with marriage duration and working period under 5 years. In facing these three roles, time management as well as family cooperation should be applied in every responsibility those three roles demand and are essential to make these roles work well.